Pendekatan Saintifik Melalui Strategi Pembelajaran Kooperatif tipe Two Stay Two Stray Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - Jumardan, Jumardan; Yuniawan, Tommi; Handayani, Sri Sularti Dewanti (Universitas Negeri Makassar, 2021)
. The purpose of this study was to analyze the effectiveness of the implementation of the scientific approach through the cooperative learning strategy of the two stay two stray type in improving the science learning outcomes of fifth-grade elementary school students and the obstacles faced by teachers and students. The type of research used is mixed methods with sequential explanatory design. The research instruments used were learning outcomes tests, observations, interviews, and documentation. The data analysis technique used is the paired sample t-test and the N-Gain test. The results showed that the value of the pretest and posttest results on Sig. (2-tailed) each school scored 0.000 or greater than 0.05, which means Ho is rejected and H1 is accepted. While in the N-gain test, SDN 20 Buton increased by 0.57 from 48.80 to 78.06 which was in the medium category, while SDN 67 Buton increased by 0.56 from 51.18 to 78.92 which was in the category currently. Thus, it can be concluded that the implementation of the scientific approach through the cooperative learning strategy of the two stay two stray type has proven to be effective in improving science learning outcomes for fifth-grade elementary school students.